Analisis Kepercayaan Diri Siswa SMPN 4 Ngamprah Melalui Pendekaan Kontruktivisme Berbantuan Aplikasi Geogebra Pada Materi Segi Empat Segitiga - Nadya Rismawati; Dea Siti Mutmainah; Nurhayati Nurhayati; Wahyu Setiawan (Journal on Education, 2019)
This study aims to analyze self-confidence in learning mathematics through a constructivism approach assisted by geogebraic applications. The research method used descriptive qualitative with the population of all students of SMPN 4 Ngamprah. The sample used was 32 students in class VIID on triangular triangle material. The instrument used is a scale of self-confidence with 25 questions that have positive responses or negative responses. The self-confidence scale is used to find responses from respondents to students' self-confidence in mathematics learning in triangle triangle material using a constructivism approach assisted by geogebraic applications. The results of this study show that the level of self-confidence of students in triangle triangle material with the help of geogebra applications shows positive results with a response rate of 61%. The average is obtained by each indicator of the confidence questionnaire that has been given to each respondent